2018
DOI: 10.1016/j.jped.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ physical activity is associated with previous and current physical activity practice by their parents

Abstract: The current and previous physical activities of parents were associated with higher levels of physical activity in adolescents, even after controlling for confounding factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 25 publications
1
20
0
2
Order By: Relevance
“…Ebeveyn fiziksel aktivite alışkanlıklarının adölesanların fiziksel aktivite alışkanlıklarını etkilediği raporlanmıştır. 24 Dinç ve ark. tarafından yapılan bir çalışmada, eğitim düzeyi yüksek olan ebeveynin, çocuklarının spor faaliyetlerine katılım ları konusunda daha bilinçli oldukları belirtilmiştir.…”
Section: Discussionunclassified
“…Ebeveyn fiziksel aktivite alışkanlıklarının adölesanların fiziksel aktivite alışkanlıklarını etkilediği raporlanmıştır. 24 Dinç ve ark. tarafından yapılan bir çalışmada, eğitim düzeyi yüksek olan ebeveynin, çocuklarının spor faaliyetlerine katılım ları konusunda daha bilinçli oldukları belirtilmiştir.…”
Section: Discussionunclassified
“…The reasons for lack of PA in the population under study include low perceived sensitivity, economic problems, physical disability for PA, wastage of free time on school, low level of exposure to the optimal models of PA at school and home (lack of access to optimal models), lack of motivation, influence of friends and classmates activity and self-efficacy in PA, place of residence, lack of access to facilities, and not being aware of the benefits of PA [ 4 ]. The earlier studies, including Anderson et al, in 2018, reported the positive role of parents as an effective environmental factor which plays the role of the model for the students in improving PA [ 1 ]. These results have also been reported by Teymouri et al, (2008) in which 65% of the students under study had acceptable PA (stages of action and maintenance), [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results of the study showed that about 30% of the students have a BMI higher than the normal level, and this points to the importance of planning for the improvement of PA and reduction of BMI in this group through designing suitable interventions. Moreover, Designing and implementing interventional programs emphasising the role of self-efficacy, and the inclusion of parents in the programs can promote regular PA in students [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several determinants associated with regular engagement in PA, including parental support, school environment, active commuting, leisure activity and available places for PA practice 5,6 . For evidence-based planning of public health interventions it is important to understand these determinants of PA behavior as well as the context in which they occur 7 .…”
Section: Introductionmentioning
confidence: 99%